Partisipasi Masyarakat Kampung Arar dalam Pengadaan Tanah untuk Pembangunan Bagi Kepentingan Umum di KEK Sorong Provinsi Papua Barat Daya - Ibal, La; Murni; Madaul, Rahful A.; Abubakar, Endang; Edwar, Rizka Cintya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Land acquisition for the construction of the Sorong SEZ will be carried out in 2023. In the development plan, the land area required for the Sorong SEZ development plan reaches 523.7 ha, which is the property of the Kami clan. The object of land acquisition for this development consists of community land in Arar village with mixed garden land conditions. This community service activity aims to increase awareness and participation of the Arar Village community in the land acquisition process for public interest development in the Sorong Special Economic Zone (KEK), Southwest Papua. This community activity was held on February 1, 2024, at the Arar Village Meeting Hall and the Sorong KEK location. This community service activity is carried out with several activities, namely: (1) preparation for the activity location and preparation of presentation materials to be delivered; (2) licensing administration and outreach to the Arar Village Government, Babinsa, and the community; (3) carrying out outreach activities at the Arar Village Meeting Hall regarding the importance of community participation in land acquisition for public purposes in the Sorong SEZ; and (4) implementation of activities and inspection of affected locations, significantly growing plants and buildings at the Sorong KEK location. The implementation of land acquisition for the construction of the Sorong SEZ went smoothly, driven by the active participation of the people of Kampung Arar. Therefore, the recommendations for this activity are: (a) Land acquisition activities are very complex activities, requiring good synergy between the government and the community; and (b) In implementing land acquisition activities, the approach taken to the community is not only carried out formally but can also be carried out informally so that the community can fully participate in development in the community area.